EFEKTIVITAS MODEL COOPERATIVE LEARNING TIPE TEAM GAME TOURNAMENT TERHADAP HASIL BELAJAR SISWA DENGAN BANTUAN MEDIA EDUCAPLAY - Dewi, Ellya Kusna Aura; Azizah, Devi Nur; Ratnasari, Diah Ayu; Khasanah, Elok Rosyidatul; Faqih, Fauziah Nur; Khumairoh, Fidyah Nur; Hanafi, Yusuf; Kustia, Cahyaning Pininta (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The objective of this study is to determine the effectiveness of the cooperative learning model of the TGT (Teams Games Tournament) type assisted by Educaplay media in improving the learning outcomes of Class IX.8 students at SMPN 3 Malang. This research is based on the need to select a more suitable learning model for theoretical materials, such as the topic